Peran On the Job Training dan Psychological Ownership Terhadap Employee Engagement dengan Kinship sebagai Pemediasi - Kefi, Darwin Yopie; Sanga, Marianus Hendrilensio; Seran, Patrisius (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2024)
The study aims to investigate on-the-job training and psychological ownership in Micro, Small, and Medium Enterprises (MSMEs) in ApasA, Kupang City, NTT. It employs a quantitative approach using questionnaires for data collection. Probability sampling method was used with a sample size of 42 individuals. Data analysis utilized Structural Equation Modeling-Partial Least Square (SEM-PLS) through Smart PLS version 3 software. Results show that on-the-job training does not significantly influence employee engagement, but psychological ownership positively impacts it. Kinship does not mediate the relationship between training or psychological ownership and employee engagement. These findings can help MSME management design more efficient human resource development strategies.